Комплекс для исследования центральной нервной системы человека - Фирсов, А. Г. (Weber, 2010)
We describe a system for research of psycho physiological conduction of human CNS. The system allows to measure critical frequency of the flashing confluence, mobility, power and dynamics of nervous system.
Keywords: центральная нервная система